Investigation of turbulence slapping technique effect on the flow behavior in pipelines - Thong, Li Mun (2010)
Cost is a very famous topic that always is the most significant factor to be concern in order to build up a piping system. Pumping power needed to pump fluid along the pipelines is increase to overcome the pressure drop of the fluid inside the pipeline. In this investigation, a fins is introduce to overcome the pumping power loses and increase the percentage of drag reduction (DR%). This investigation had undergo with a liquid circulation system where a smooth PVC pipe with 0.00381m I.D to rough galvanized iron with 5 pressure sensor which located 0.5m distance each pressure sensor. Fins model is an object where a stainless steel ring connected with 4 chains with few plastic plates. It is installing inside the 0.00381m I.D PVC pipe. The experiment was run for 2 minutes at several fluid velocities. The highest Dr% from the experiment is 78.51%. The investigation had successful to prove the blending fins are high potential to replace chemical drag reducer in pipelines to reduce pumping power losses.